Functional Fitness in older Healthy Individuals and those who suffered a Stroke: a prospective observational study - Diane E. Adamo; Alicia Jones (Advances in Social Sciences Research Journal, 2019)
Question: What is the risk for loss of functional independence in individuals who suffered a stroke and healthy older adults? What physical performance measures indicate the greatest loss of functional independence for both groups? Design: Prospective, observational study. Participants: Fourteen individuals who suffered a stroke and 14 age-matched healthy controls. Outcome measures: Six performance measures (chair stand, arm curl, chair sit and reach, back scratch, 6-minute walk/2-minute march-in-place and 8-foot up and go) that comprise the Senior Fitness Test (SFT). Results: Individuals who suffered a stroke showed reduced lower body flexibility (CI [1.2 – 9.1]; p < 0.05) and took longer to perform the timed up and go task than healthy controls (CI [.18 - 11.5]; p < 0.05). Upper and lower body strength, endurance and upper body flexibility were similar between groups. However, 91% of individuals with a stroke and 71% of the healthy controls were at risk for functional loss on at least 4 / 6 SFT items. Conclusions: To delay the progressive loss of independence and eventual placement in residential care or assisted living facilities, both groups would benefit from understanding the physical attributes that place them at risk for functional loss. Thus, we propose the use of the Senior Fitness Test to identify physical attributes that place individuals at risk for loss of independence that, in turn, will help them to develop task-specific fitness goals.